1)Let's find "\\theta_0" an angle of intersection between the curves:
"r_1(\\theta)-r_2(\\theta) = 0 = a(1-cos(\\theta))-2a(cos(\\theta))=a(1-3cos(\\theta))\n\\implies \\theta_0 = arccos(\\cfrac{1}{3})"
2)Now let's calculate "m_1" and "m_2" :
"m_1=\\cfrac{\\cfrac{dr_1(\\theta_0)}{d\\theta}sin(\\theta)+r_1(\\theta_0)cos(\\theta_0)}{\\cfrac{dr_1(\\theta_0)}{d\\theta_0}cos(\\theta_0)-r_1(\\theta_0)sin(\\theta_0)}=\\cfrac{sin^2(\\theta_0)+r_1(\\theta_0)cos(\\theta_0)}{sin(\\theta_0)cos(\\theta_0)-r_1(\\theta_0)sin(\\theta_0)}=\\cfrac{a(\\cfrac{2\\sqrt2}{3})^2+\\cfrac{2}{9}a}{\\cfrac{2\\sqrt2}{9}a-\\cfrac{4\\sqrt2}{9}a}=\\cfrac{-5\\sqrt2}{2}"
"m_2=\\cfrac{\\cfrac{dr_2(\\theta_0)}{d\\theta}sin(\\theta)+r_2(\\theta_0)cos(\\theta_0)}{\\cfrac{dr_2(\\theta_0)}{d\\theta_0}cos(\\theta_0)-r_2(\\theta_0)sin(\\theta_0)}=\\cfrac{-2sin^2(\\theta_0)+r_2(\\theta_0)cos(\\theta_0)}{-2sin(\\theta_0)cos(\\theta_0)-r_2(\\theta_0)sin(\\theta_0)}=\\cfrac{-2a(\\cfrac{2\\sqrt2}{3})^2+\\cfrac{2}{9}a}{\\cfrac{-4\\sqrt2}{9}a-\\cfrac{4\\sqrt2}{9}a}=\\cfrac{-7\\sqrt2}{8}"
Then angle "\\alpha" of intersection between the two curves is:
"\\alpha=arctan|\\cfrac{m_1-m_2}{1+m_1m_2}|=arctan|\\cfrac{-\\cfrac{13\\sqrt2}{8}}{\\cfrac{86}{16}}|\n=arctan|\\cfrac{-13\\sqrt2}{43}|"
Answer: "\\alpha=arctan|\\cfrac{-13\\sqrt2}{43}|=arctan(\\cfrac{13\\sqrt2}{43})."
Comments
Leave a comment